Politik Hukum Pengaturan Keserentakan Pemilu - Abdul Basid Fuadi (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
General elections in Indonesia have shifted a lot motivated by efforts to seek their ideal form. The last time, elections were held simultaneously by combining the five types of elections stipulated in Article 22E of the 1945 Constitution. The various complexities and challenges of the 2019 election should be evaluated. Elections basically have two main objectives, 1) to produce a government that represents every element in society; 2) create a government that is able to govern well. This paper discusses about the complexity and challenges of the 2019 simultaneous election and how the ideal election timing is designed. This research uses normative legal research methods (legal research) with two approaches: normative approach and conceptual approach. This study resulted, first, there were technical complications in the 2019 Concurrent Election, namely the workload of the organizers, especially the KPPS; a significant increase in the election budget; and voter confusion due to too many types of elections which implicated too many candidate lists. Second, the Constitutional Court has determined six electoral models as well as constitutional ones, and this can be considered as judicial law politics. Lawmakers must immediately act on the Constitutional Court's decision by amending the electoral law which adopts one of the simultaneous election models.